Proteomic and lipidomic analyses of the Arabidopsis atg5 autophagy mutant reveal major changes in endoplasmic reticulum and peroxisome metabolisms and in lipid composition. Issue 3 (22nd June 2019) - Havé, Marien; Luo, Jie; Tellier, Frédérique; Balliau, Thierry; Cueff, Gwendal; Chardon, Fabien; Zivy, Michel; Rajjou, Loic; Cacas, Jean‐Luc; Masclaux‐Daubresse, Céline
Summary: Autophagy is a universal mechanism in eukaryotic cells that facilitates the degradation of unwanted cell constituents and is essential for cell homeostasis and nutrient recycling. The salicylic acid‐independent effects of autophagy defects on leaf metabolism were determined through large‐scale proteomic and lipidomic analyses of atg5 and atg5/sid2 mutants under different nitrogen and sulfur growth conditions. Results revealed that irrespective of the growth conditions, plants carrying the atg5 mutation presented all the characteristics of endoplasmic reticulum (ER) stress. Increases in peroxisome and ER proteins involved in very long chain fatty acid synthesis and β‐oxidation indicated strong modifications of lipid metabolism. Lipidomic analyses revealed changes in the concentrations of sphingolipids, phospholipids and galactolipids. Significant accumulations of phospholipids and ceramides and changes in GIPCs (glycosyl‐inositol‐phosphoryl‐ceramides) in atg5 mutants indicated large modifications in endomembrane‐lipid and especially plasma membrane‐lipid composition. Decreases in chloroplast proteins and galactolipids in atg5 under low nutrient conditions, indicated that chloroplasts were used as lipid reservoirs for β‐oxidation in atg5 mutants. In conclusion, this report demonstrates the strong impact of autophagy defect on ER stress and reveals the role of autophagy in the control of plant lipid metabolism and catabolism, influencing both lipid homeostasis and endomembrane composition.